2018
DOI: 10.1097/pec.0000000000001621
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intraosseous Access Performed by Emergency Department Nurses Using Semiautomatic Devices

Abstract: Background:No study has examined the performance of emergency department (ED) nurses in establishing intraosseous access (IO) access. This study aimed to evaluate ED nurses' success rate in establishing pediatric IO access using semiautomatic devices. Methods:A randomized crossover simulation study was conducted. The success rates of ED nurses were compared with those of paramedics with similar years of experience. The study instruments were the new springloaded injector (NIO) and the battery power drill (EZ-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…El-Nawawy et al [ 25 ] in a study analysing intravascular access in paediatric septic shock patients indicated that the success rate of the first attempt of IV and intraosseous access was varied and amounted to 50% and 100%, respectively. As implied by Feldman et al [ 26 ], paramedics presented a slightly higher insertion success rates in intraosseous access compared with emergency department nurses in a paediatric bone model (83.3% vs. 79.4%); the effectiveness of obtaining access equalled 80% vs. 70.6% for the NIO-P intraosseous access device and 86.7% vs. 88.2% for EZ-IO. Szarpak et al [ 27 ] observed the effectiveness of NIO-P, EZ-IO, and Jamshidi at the level of 100%, 97%, and 43%, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…El-Nawawy et al [ 25 ] in a study analysing intravascular access in paediatric septic shock patients indicated that the success rate of the first attempt of IV and intraosseous access was varied and amounted to 50% and 100%, respectively. As implied by Feldman et al [ 26 ], paramedics presented a slightly higher insertion success rates in intraosseous access compared with emergency department nurses in a paediatric bone model (83.3% vs. 79.4%); the effectiveness of obtaining access equalled 80% vs. 70.6% for the NIO-P intraosseous access device and 86.7% vs. 88.2% for EZ-IO. Szarpak et al [ 27 ] observed the effectiveness of NIO-P, EZ-IO, and Jamshidi at the level of 100%, 97%, and 43%, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Gaining vascular access is of critical importance in resuscitative, therapeutic, and diagnostic measures [ 8 , 9 ]. IO cannulation is the first-line alternative technique in gaining vascular access in critically ill patients when central or peripheral venous access is unattainable in both hospital and pre-hospital conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this review suggest that IO access should be considered for hypotensive trauma patients, especially those who are under severe hypovolemic shock [ 4 ]. Multiple studies show high success rates by physicians, nurses, and paramedics in performing IO cannulation of adults and pediatric patients [ 7 , 8 ]. In fact, studies have shown there is no statistically significant difference in complications between the IO and IV interventions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IO access in critical patients with severe hypotension seems to have a higher success rate compared to a traditional venous access; hence, IO access should be considered an alternative priority 2,3 . However, despite the literature underlines that IO access may be easily learnt by the healthcare sta , this procedure is still scarcely used 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%